Betulinic acid derivatives NVX-207 and B10 for treatment of glioblastoma–an in vitro study of cytotoxicity and radiosensitization - Bache, Matthias; Bernhardt, Stephan; Passin, Sarina; Wichmann, Henri; Hein, Anja; Zschornak, Martin; Kappler, Matthias; Taubert, Helge; Paschke, Reinhard; Vordermark, Dirk (International Journal of Molecular Sciences, 2014)
Betulinic acid (BA), a pentacyclic triterpene, represents a new therapeutic substance that has potential benefits for treating glioblastoma. Recently, new strategies for producing BA derivatives with improved properties have evolved. However, few studies have examined the combination of BA or BA derivatives using radiotherapy. The effects of two BA derivatives, NVX-207 and B10, on cellular and radiobiological behavior were analyzed using glioblastoma cell lines (U251MG, U343MG and LN229). Based on IC50 values under normoxic conditions, we detected a 1.3-2.9-fold higher cytotoxicity of the BA derivatives B10 and NVX-207, respectively, compared to BA. Incubation using both BA derivatives led to decreased cell migration, cleavage of PARP and decreased protein expression levels of Survivin. Weak radiation sensitivity enhancement was observed in U251MG cells after treatment with both BA derivatives. The enhancement factors at an irradiation dose of 6 Gy after treatment with 5 µM NVX-207 and 5 µM B10 were 1.32 (p=0.029) and 1.55 (p=0.002), respectively. In contrast to BA, neither NVX-207 nor B10 had additional effects under hypoxic conditions. Our results suggest that the BA derivatives NVX-207 and B10 improve the effects of radiotherapy on human malignant glioma cells, particularly under normoxic conditions.
EVALuna2:16313